Regulatory T cell-deficient scurfy mice develop systemic autoimmune features resembling lupus-like disease - Hadaschik, Eva; Wei, Xiaoying; Leiss, Harald; Heckmann, Britta; Niederreiter, Birgit; Steiner, Günter; Ulrich, Walter; Enk, Alexander; Smolen, Josef S.; Stummvoll, Georg (Arthritis Research & Therapy, 2015)
Scurfy mice are deficient in regulatory T cells (Tregs), develop a severe, generalized autoimmune disorder that can affect almost every organ and die at an early age. Some of these manifestations resemble those found in systemic lupus erythematosus (SLE). In addition, active SLE is associated with low Treg numbers and reduced Treg function, but direct evidence for a central role of Treg malfunction in the pathophysiology of lupus-like manifestations is still missing. In the present study, we characterize the multiorgan pathology, autoantibody profile and blood count abnormalities in scurfy mice and show their close resemblances to lupus-like disease.
Gesehen am 01.03.2021